(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
There is no satisfactory preoperative tools to differentiate a benign from malignant masses in pelvis. Serum CAl25 level, pelvic ultrasonogram and menopausal status are used individually to predict malignancy with poor outcome but the use of three in association RMI can improve diagnostic performance. Objective:- To evaluate RMI scoring system as method of choice for predicting whether or not an ovarian mass is likely to be malignant. Design:- Cross sectional study. Settings:- Chittagong medical college hospital and Chittagong metropolitan hospital. Duration: January 2011 to October 2014. Sample size:-175 patients admitted in January 2011 to October 2014. The risk malignancy index was calculated as UXMXCA 125 performed preoperatively. Ultrasound findings were scored depending on wall structure, wall thickness and echogenecity (1,4), Menopausal status pre and post menopausal scored as (1,4) and absolute level of CA 125 measured by radioimmunoassay. The individual performance were found in RMI (sen82%, spe 77%, +ve PV 81%, -vePV23, +veLR5.s6, -veL. 53, accuracy 78%), USG (sen86%, spe23%, +vePV87%, vePV32%, +veLR6.5%, veLR.84, accuracy 82%), CAl25 (sen72%, spe32%, +vePV87%, vePV32%, +veLR6.5, veLR. 84, accuracy 67%), Manupausal status (sen84%, spe50%, +vePV21%, -vePV2.4%, +veLR, -veLR, accuracy78%). The area under the ROC curve for risk malignancy index was (.8-.9), which was greater than the area for CAl25 (.6-.7), USG (.7-.8) score and menopausal status (.7-.8). The risk malignancy index using ultrasound morphological score, serum CAl25 level and menopausal status might be of value in the preoperative assessment of ovarian carcinoma. JCMCTA 2014 ; 25 (2) : 14-20